2022
DOI: 10.3389/frlct.2022.1035423
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical device to control sample pH locally in Lab-on-PCB devices: An investigation into spatial resolution

Abstract: During the recent pandemic outbreak, Lab-on-Chip devices did not manage to fully reach their potential in rapid diagnosis of pathogens, mainly due to the lack of cost-effective LoC solutions integrated with all required sample preparation modules. This paper presents such a critical step, aiming to translate electrochemical pH control into practical protein preconcentration modules, easy to integrate with subsequent quantification modules seamlessly via Lab-on-PCB technology. In this work we present a device c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…7 Notably, cyclization of FAM has also been reported; however, the pH window under which FAM is in the open, fluorescent form is between 6 and 9, enhancing its applicability in biological assays. 6,8 4,4-Difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) being another widely applied fluorescent core has also found application in many different fields. 9 Due to their generally relatively sharp fluorescence peaks, high quantum yields, and additional insensitivity to pH and other environmental conditions, prematurely, they have found great application in biological studies and are widely used to label peptides and proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Notably, cyclization of FAM has also been reported; however, the pH window under which FAM is in the open, fluorescent form is between 6 and 9, enhancing its applicability in biological assays. 6,8 4,4-Difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) being another widely applied fluorescent core has also found application in many different fields. 9 Due to their generally relatively sharp fluorescence peaks, high quantum yields, and additional insensitivity to pH and other environmental conditions, prematurely, they have found great application in biological studies and are widely used to label peptides and proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
“…When FAM is coupled to the N-terminus of a peptide forming an amide bond, its two carboxylic acids result in the possibility of the formation of two inseparable isomers; however, it was shown that incorporation of FAM can result in an increase in sensitivity compared to the other commonly used fluorescein derivative, fluorescein isothiocyanate (FITC), making it a viable alternative to RhoB and FITC . Notably, cyclization of FAM has also been reported; however, the pH window under which FAM is in the open, fluorescent form is between 6 and 9, enhancing its applicability in biological assays. , 4,4-Difluoro-4-bora-3a,4a-diaza- s -indacene (BODIPY) being another widely applied fluorescent core has also found application in many different fields . Due to their generally relatively sharp fluorescence peaks, high quantum yields, and additional insensitivity to pH and other environmental conditions, prematurely, they have found great application in biological studies and are widely used to label peptides and proteins. For our application, the BODIPY core can be modified to carry a carboxylic acid on one of its pyrrole functionalities, giving rise to BODIPY-FL-propanoic acid (Figure a), , which can be directly applied for amide bond formation in peptide synthesis.…”
Section: Introductionmentioning
confidence: 99%